Surviving ChatGPT in healthcare - Liu, Zhengliang; Zhang, Lu; Wu, Zihao; Yu, Xiaowei; Cao, Chao; Dai, Haixing; Liu, Ninghao; Liu, Jun; Liu, Wei; Li, Quanzheng; Shen, Dinggang; Li, Xiang; et al. (Frontiers in Radiology, 2024)
At the dawn of of Artificial General Intelligence (AGI), the emergence of large language models such as ChatGPT show promise in revolutionizing healthcare by improving patient care, expanding medical access, and optimizing clinical processes. However, their integration into healthcare systems requires careful consideration of potential risks, such as inaccurate medical advice, patient privacy violations, the creation of falsified documents or images, overreliance on AGI in medical education, and the perpetuation of biases. It is crucial to implement proper oversight and regulation to address these risks, ensuring the safe and effective incorporation of AGI technologies into healthcare systems. By acknowledging and mitigating these challenges, AGI can be harnessed to enhance patient care, medical knowledge, and healthcare processes, ultimately benefiting society as a whole.